2018
DOI: 10.1089/ast.2017.1739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Compounds on Dissolution of the Phosphate Minerals Chlorapatite, Whitlockite, Merrillite, and Fluorapatite: Implications for Interpreting Past Signatures of Organic Compounds in Rocks, Soils and Sediments

Abstract: Phosphate is an essential nutrient for life on Earth, present in adenosine triphosphate (ATP), deoxyribonucleic acid (DNA), ribonucleic acid (RNA), and phospholipid membranes. Phosphorus does not have a significant volatile phase, and its release from minerals is therefore critical to its bioavailability. Organic ligands can enhance phosphate release from minerals relative to release in inorganic solutions, and phosphorus depletion in paleosols has consequently been used as a signature of the presence of ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…Results from Model 1, designed to test differences in serpentinite reactivity in inorganic, abiotic-organic, and biotic systems, show that across a wide range of temperatures, Mg and Si release from serpentinite in the presence of biotic acids is significantly enhanced compared with Mg and Si release in the presence of nitric acid (Figure 1A,B; Table 2). This is consistent with previous laboratory and terrestrial field studies that show that organic acids accelerate mineral weathering [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Biotically Enhanced Serpentinite Dissolutionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results from Model 1, designed to test differences in serpentinite reactivity in inorganic, abiotic-organic, and biotic systems, show that across a wide range of temperatures, Mg and Si release from serpentinite in the presence of biotic acids is significantly enhanced compared with Mg and Si release in the presence of nitric acid (Figure 1A,B; Table 2). This is consistent with previous laboratory and terrestrial field studies that show that organic acids accelerate mineral weathering [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Biotically Enhanced Serpentinite Dissolutionsupporting
confidence: 93%
“…On Earth, studies have shown that organic acids produced by microorganisms and plants enhance mineral dissolution rates in weathering environments [28][29][30][31][32][33][34][35][36][37][38][39]. In addition to accelerated dissolution, some trace elements may be preferentially released in the presence of organic acids during water-rock interaction [36,[40][41][42], which may result in a preserved record of mineral-microbe interactions.…”
Section: Introductionmentioning
confidence: 99%
“…1). The same has been observed with acetate in a previous study (Bartlett et al, 2018). Formates and carbonates generated more concentrated phosphate solutions than the experiments in the absence of these chemicals at pH 8.…”
Section: Effects Of Formates and Carbonates On Ribose Phosphorylationsupporting
confidence: 88%
“…Laboratory experiments have demonstrated the effect of organic acids on phosphatebearing whole rocks [7,[239][240][241] as well as individual minerals in the presence of organic compounds [242][243][244][245][246][247] including the Mars-relevant Ca-phosphate-bearing minerals fluorapatite, merrillite, and whitlockite [248]. The dissolution of apatite-bearing rocks in the presence of organic compounds has shown enhancement of phosphate release in the presence of acetate, benzoate, citrate, formate, fumarate, gallate, glutarate, lactate, malonate, oxalate, phthalate, salicylate, and succinate [7,[239][240][241].…”
Section: Biological Mobilization Of Phosphorus (P)mentioning
confidence: 99%
“…The dissolution of apatite-bearing rocks in the presence of organic compounds has shown enhancement of phosphate release in the presence of acetate, benzoate, citrate, formate, fumarate, gallate, glutarate, lactate, malonate, oxalate, phthalate, salicylate, and succinate [7,[239][240][241]. The dissolution of fluorapatite in experiments containing organic compounds has indicated enhanced dissolution in the presence of acetate, citrate, oxalate, phthalate, and salicylate [243,246], and the dissolution of multiple Ca phosphate minerals relevant to Mars in experiments containing organic compounds relevant to Mars has indicated that the enhancement of dissolution by the organic compounds is likely due to the ligand denticity, the strength of the complex formed between the organic compound and calcium, and the saturation state of the solution [248]. The dissolution of hydroxyapatite in the presence of amino acids has indicated enhanced release of phosphate in the presence of aspartic acid but not alanine or lysine, which is attributed to the charge on the amino acids [244].…”
Section: Biological Mobilization Of Phosphorus (P)mentioning
confidence: 99%